Steroid; β- Sitosterol from Corydalis govaniana (Wall) growing Himalayan region of Nepal - Shrestha, R.L. Swagat; Jha, R. N. (Journal of Nepal Chemical Society, 2013)
The Himalayan plant Corydalis govaniana (Wall) commonly known as Bhutkesi in Hindi on detail chemical investigation led to the isolation of β-sitosterol and its structure was determined by detail spectroscopic analysis. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9253 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 62-66 Uploaded date: 12/5/2013